Baking soda over 500 fabulous, fun and frugal uses you've probably never thought of - Lansky, Vicki (Minnetonka, MN Book Peddlers, 1995)
The Good Cook Book Club, 6/99
Keywords: Home economics--Miscellanea; Sodium compounds--Miscellanea